A label-free electrochemical aptasensor based on leaf-like vanadium disulfide-Au nanoparticles for the sensitive and selective detection of platelet-derived growth factor BB. Issue 19 (7th October 2015) - Liu, Xue; Shuai, Hong-Lei; Huang, Ke-Jing
<x xml:space="preserve">Abstract</x> In this work, an electrochemical aptasensor for the sensitive detection of platelet-derived growth factor BB (PDGF-BB) is fabricated based on leaf-like VS2 nanosheets which are prepared by a facile hydrothermal method.